Study of antidepressant effects of grape seed oil in male mice using tail suspension and forced swim tests - Rabiei, Zahra; Naderi, Sajad; Rafieian-Kopaei, Mahmoud (Bangladesh Journal of Pharmacology, 2017)
The aim of this study was to investigate the antidepressant effects of grape seed oil in male mice (n=60) using tail suspension and forced swim tests. Mice were divided to six groups of 10 in each group. Group I: Intraperitoneally receiving normal saline; Group II: Received normal saline & stress; Group III-V: Injected (i.p.) with different (60, 120, and 240 mg/kg) doses of grape seed oil; and Group VI: Received fluoxetine (10 mg/kg). Grape seed oil in 60 mg/kg significantly decreased immobility time in tail suspension and forced swim tests under chronic unpredictable stress compared to groups under chronic stress receiving normal saline and grape seed oil (120 and 240 mg/kg). Grape seed oil (60 mg/kg) significantly improved the motor balance in mice under chronic stress. It had no significant effect on serum corticosterone level. Grape seed oil can improve depression symptoms in mice. Video Clip of Methodology: 0 min 14 sec Click to watch